Analysis of powder diffraction data collected with synchrotron X-ray and multiple 2D X-ray detectors applying a beta-distribution peak profile model. (5th September 2017) - Ida, Takashi; Wachi, Kento; Hattan, Daiki; Ono, Shoki; Tachiki, Shoji; Nakanishi, Yuki; Sakuma, Yasuhiro; Wada, Akio; Towata, Shin-ichi
Abstract : A powder diffraction measurement system constructed on a beam-line BL5S2 at Aichi Synchrotron Radiation Center in Seto, Japan, has been modified for extensive use of two-dimensional (2D) X-ray detectors. Four flat 2D detectors are currently mounted on the movable stages on supporting rods radially attached to the 2Θ-wheel of the goniometer with the interval of 25°. The 2D powder diffraction intensity data are reduced to conventional 1D format of powder diffraction data by the method based on averaging of the pixel intensities with geometrical corrections, which also enables evaluation of standard uncertainties about the reduced intensity data. The 1D powder diffraction data of a 0.1 mm-capillary LaB6 (NIST SRM660b) sample obtained at the camera length of 340 mm have shown almost symmetric peak profile with slight asymmetry simulated by a beta-distribution profile function.